Cardiovascular Effects of Micromeria graeca (L.) Benth. ex Rchb in Normotensive and Hypertensive Rats - Akdad, Mourad; Eddouks, Mohamed (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2020)
Aims: The present study was performed in order to analyze the antihypertensive activity of Micromeria graeca (L.) Benth. ex Rchb. Background: Micromeria graeca (L.) Benth. ex Rchb is an aromatic and medicinal plant belonging to the Lamiaceae family. This herb is used to treat various pathologies such as cardiovascular disorders. Meanwhile, its pharmacological effects on the cardiovascular system have not been studied. Objective: The present study aimed to evaluate the effect of aqueous extract of aerial parts of Micromeria graeca (AEMG) on the cardiovascular system in normotensive and hypertensive rats. Methods: In this study, the cardiovascular effect of AEMG was evaluated using in vivo and in vitro investigations. In order to assess the acute effect of AEMG on the cardiovascular system, anesthetized L-NAME-hypertensive and normotensive rats received AEMG (100 mg/kg) orally and arterial blood pressure parameters were monitored during six hours. In the sub-chronic study, rats were orally treated for one week, followed by blood pressure assessment during one week of treatment. Blood pressure was measured using a tail-cuff and a computer-assisted monitoring device. In the second experiment, isolated rat aortic ring pre-contracted with Epinephrine (EP) or KCl was used to assess the vasorelaxant effect of AEMG. Results: Oral administration of AEMG (100 mg/kg) provoked a decrease of arterial blood pressure parameters in hypertensive rats. In addition, AEMG induced a vasorelaxant effect in thoracic aortic rings pre-contracted with EP (10 μM) or KCl (80 mM). This effect was attenuated in the presence of propranolol and methylene blue. While in the presence of glibenclamide, L-NAME, nifedipine or Indomethacin, the vasorelaxant effect was not affected. Conclusion: This study showed that Micromeria graeca possesses a potent antihypertensive effect and relaxes the vascular smooth muscle through β-adrenergic and cGMP pathways.
Keywords: Micromeria graeca